Advances in decision analysis - "Edwards, Ward (ed.)" (New York, 2007)
Decision analysis is a prescriptive theory that aids individuals or groups confronted with complex problems in a wide variety of contexts. By framing issues, identifying risks, eliciting stakeholder preferences, and suggesting alternative approaches, decision analysts can offer workable solutions in domains such as the environment, health and medicine, engineering and operations research, and public policy. This book is a mixture of historical and forward-looking essays on key topics in decision analysis. Part I covers the history and foundations of decision analysis. Part II discusses structuring decision problems, including the development of objectives and their attributes, and influence diagrams. Part III discusses probabilities and their elicitation and Bayes nets. Part IV discusses additive and multiplicative utilities, risk preferences, and 'option pricing' methods. Part V discusses risk analysis. Part VI puts decision analysis in a behavioral and organizational context. Part VII presents case studies of applications.
Keywords: Decision making